Geographic patterns of Acinetobacter baumannii and carbapenem resistance in the Asia-Pacific Region: results from the Antimicrobial Testing Leadership and Surveillance (ATLAS) program, 2012-2019. (February 2023) - Lee, Yu-Lin; Ko, Wen-Chien; Hsueh, Po-Ren
Highlights: The prevalence of carbapenem-resistant Acinetobacter baumannii (CR-AB) varied among countries. Of 232 CR-AB isolates, 224 (96.6%) harbored at least one carbapenemase gene. Of the 226 carbapenemase genes detected, bla OXA-23 was the most dominant (94.7%). CR-AB showed varied resistance rates for minocycline, colistin, and tigecycline. ABSTRACT: Objectives: This study aimed to investigate the geographic distribution of carbapenem-resistant Acinetobacter baumannii (CR-AB) isolates in the Asia-Pacific region. Methods: We collected A. baumannii isolates using the Antimicrobial Testing Leadership and Surveillance program from 2012 to 2019. The minimum inhibitory concentrations (MICs) of the isolates were determined using the broth microdilution method. The major carbapenemase genes were identified using multiplex polymerase chain reaction assays for the isolates collected between 2012 and 2014. CR-AB was defined as isolates with meropenem MICs ≥8 mg/l. Results: In total, 2674 A. baumannii isolates were collected from 13 countries, of which 1918 (71.7%) were CR-AB. The carbapenem resistance rates among A. baumannii isolates were as low as 2.8% and 6.5% in Japan and Australia, respectively, but as high as 88% and 87.2% in South Korea and India, respectively. Of the 232 CR-AB isolates that underwent carbapenemase gene screening, 224 (96.6%) harbored at least one carbapenemase gene. A total of 226 carbapenemase genes were detected, with bla OXA-23 (94.7%, 214/226) being the most dominant, followed by bla OXA-72 (2.7%, 6/226), bla OXA-58 (2.2%, 5/226), and bla NDM-1 (0.4%, 1/226) . CR-AB isolates had >80% resistance to amikacin, ampicillin/sulbactam, cefepime, ceftazidime, ciprofloxacin, levofloxacin, and piperacillin/tazobactam. The rates of CR-AB resistance to minocycline and colistin were 7.2% (31/429) and 1.7% (23/1368). For cefoperazone/sulbactam and tigecycline, 50.2% (527/1049) and 93.3% (1789/1918) of CR-AB isolates had an MIC ≤16 mg/l and ≤2 mg/l, respectively. Conclusion: The prevalence of carbapenem resistance in A. baumannii showed significant differences among countries in the Asia-Pacific region, and the treatment options were limited.